Impact of interval from breast conserving surgery to radiotherapy on local recurrence in older women with breast cancer: retrospective cohort analysis. (2nd March 2010) - Punglia, Rinaa S; Saito, Akiko M; Neville, Bridget A; Earle, Craig C; Weeks, Jane C
Abstract : Objectives To determine if the length of interval between breast conserving surgery and start of radiotherapy affects local recurrence and to identify factors that might be associated with delay in older women with breast cancer. Design Retrospective cohort analysis with Cox proportional hazards models to study the association between time to radiotherapy and local recurrence, and propensity score and instrumental variable analyses to confirm findings. Logistic regression investigated factors associated with later start of radiotherapy. Setting Linked database (Surveillance, Epidemiology, and End Results Program-Medicare) in the United States Participants 18 050 women aged over 65 with stage 0-II breast cancer diagnosed in 1991-2002 who received breast conserving surgery and radiotherapy but not chemotherapy. Main outcome measure Local recurrence. Results Median time from surgery to start of radiotherapy was 34 days, with 29.9% (n=5389) of women starting radiotherapy after six weeks. Just over 4% (n=734) of the cohort experienced a local recurrence. After adjustment for clinical and sociodemographic factors, intervals over six weeks were associated with increased likelihood of local recurrence (hazard ratio 1.19, 95% confidence interval 1.01 to 1.39, P=0.033). When the interval was modelled continuously (assessing accumulation of risk by day), the effect was statistically stronger (hazard ratio 1.005 per day, 1.002 to 1.008, P=0.004). Propensity score and instrumental variable analysis confirmed these findings. Instrumental variable analysis showed that intervals over six weeks were associated with a 0.96% increase in recurrence at five years (P=0.026). In multivariable analysis, starting radiotherapy after six weeks was significantly associated with positive nodes, comorbidity, history of low income, Hispanic ethnicity, non-white race, later year of diagnosis, and residence outside the southern states of the US. Conclusions There is a continuous relation between the interval from breast conserving surgery to radiotherapy and local recurrence in older women with breast cancer, suggesting that starting radiotherapy as soon as possible could minimise the risk of local recurrence. There are considerable disparities in time to starting radiotherapy after breast conserving surgery. Regions of the US known to have increased rates of breast conserving surgery had longer intervals before radiotherapy, suggesting limitations in capacity. Given the known negative impact of local recurrence on survival, mechanisms to ameliorate disparities and policies regarding waiting times for treatment might be warranted.